Advancing Injury Prevention and Athletic Performance: Bridging Biomechanics, Technology, and Rehabilitation in Sports Medicine - Wasilewska, Małgorzata; Pietrzak, Krzysztof; Polok, Sebastian (Quality in Sport, 2025)
Purpose of Research: This study examines recent advancements in sports injury prevention, rehabilitation, and performance optimization, identifying gaps between biomechanical research, technological innovation, and real-world application. It critiques systemic challenges in translating evidence into equitable, ethical, and culturally competent practices. Research Materials and Methods: A narrative review analyzed 43 peer-reviewed studies (2023–2024) from PubMed, Scopus, Web of Science, and SPORTDiscus. Keywords included sports injuries, AI in sports medicine, and telerehabilitation. Inclusion criteria prioritized original research, RCTs, and studies addressing biomechanical, technological, or sociocultural factors. Thematic analysis categorized findings into six domains, with critical appraisal using Cochrane and GRADE tools. Basic Results: Persistent injury rates (e.g., 22% ACL reinjuries) reflect oversimplified risk models and poor translation of biomechanical insights. Wearables and AI showed mixed efficacy- exoskeletons reduced lumbar strain by 30% but caused neuromuscular imbalances, while telerehabilitation succeeded only with community integration (89% adherence). Cultural resistance (e.g., Irish load management trial) and ethical dilemmas (e.g., youth bone density overtesting) underscored systemic inequities. Conclusions: Sports medicine requires interdisciplinary frameworks integrating biomechanics, technology, and cultural competence. Ethical AI, neurophysiological biomarkers, and hybrid telerehabilitation models offer pathways forward. Prioritizing athlete narratives over reductionist metrics and fostering global equity are critical to sustainable progress.